Comprehensive analysis of early pregnancy loss based on cytogenetic findings from a tertiary referral center - Xiaoqing Wu (BMC, 2021)
Abstract Background Pregnancy loss is one of the most common complications during pregnancy. Clinical consultation based on etiology analysis are critical for reducing anxiety and distress. This study aimed to perform a comprehensive analysis for products of conception (POC) in miscarriage based on genetic etiology and clinical information. Methods A retrospective study was conducted according to cytogenetic findings of 1252 POC from spontaneous pregnancy loss over 11 years. The frequencies and profiles of chromosomal abnormalities were discussed according to the classification of women with different maternal ages, previous miscarriage history, normal live birth history, and different modes of conception. Results A total of 667 (53.2%) chromosomal abnormalities were observed, including 592 (47.3%) cases of numerical abnormalities, 38 (3.0%) cases of structural abnormalities, and 37 (3.0%) cases of mosaic aberrations. In women above 40 years of age, the rates of chromosomal abnormalities and viable autosomal trisomy were significantly higher than those in women with ≤ 29, 30–34, and 35–39 years of age (p < 0.05). The frequency of abnormal karyotype in women with normal live birth history was 61.1%, significantly higher than 52.5% in women without normal live birth history (p < 0.05). There was no significant differences among women without, with 1–2, and ≥ 3 previous miscarriages regarding the rate of abnormal karyotype (p > 0.05); viable autosomal trisomy was less common in women with ≥ 3 previous miscarriages than women with < 3 miscarriages. The frequency of chromosomal abnormalities was 49.0% and 55.0% in women with assisted conception and natural conception (p > 0.05), respectively; monosomy X was more frequently detected in women with natural conception than assisted conception. Conclusion The frequencies and profiles of chromosomal abnormalities in early miscarriages are strongly associated with clinical information including maternal age, previous miscarriage, live birth history, and mode of conception. Cytogenetic analysis of POC should be recommended to women with a first miscarriage and women with normal live birth history.